Structural Transformations in Dairy Sector of India - Kaur, Manpreet; Singla, Naresh (Indian Journal of Dairy Science, 2018)
The ongoing agrarian crises and rise in demand for dairy products coupled with government’s emphasis on dairy sector since operation flood has led to shift in dynamics of crop-livestock production systems in India. In this context, the study has identified major structural transformations in dairy sector of India since 1991. The study reveals that India has witnessed a tremendous increase in milk production, rise in per capita availability of milk and change in composition of milk production across various species. The study also shows that different states of India has responded differently to the structural changes such as rapid growth in contribution of milk by states like Andhra Pradesh, Gujarat and Rajasthan in national milk production, while traditionally green revolutionary states such as Punjab and Haryana along with Karnataka, Maharashtra, Tamil Nadu, Madhya Pradesh and West Bengal have registered a decline in milk contribution. At national level, the contribution of crossbred cows has continuously increased, whereas the share of indigenous/local cows and buffaloes has gone down. The study also reveals that around 57 per cent rise in growth of milk production is contributed by increase in livestock population, while 31 per cent is attributed to increase in milk yield of the milch animals. The structural shift is also witnessed in milk marketing pattern with cooperative sector expanding its procurement and processing capacity.